2012
DOI: 10.1063/1.4742899
|View full text |Cite
|
Sign up to set email alerts
|

Exciton mediated self-organization in glass driven by ultrashort light pulses

Abstract: Local ab initio methods for calculating optical bandgaps in periodic systems. II. Periodic density fitted local configuration interaction singles method for solids J. Chem. Phys. 137, 204119 (2012) Quantum coherence effects in hybrid nanoparticle molecules in the presence of ultra-short dephasing times Appl. Phys. Lett. 101, 213102 (2012) Photoluminescence study of magnetic spin clusters and their temperature evolution in Cd0.70Mn0.30Te spinglass compound J. Appl. Phys. 112, 093715 (2012) Excitonic lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 28 publications
2
49
0
Order By: Relevance
“…The role of the chemistry in laser-induced structural glass modification was addressed in many studies [52][53][54][55][56][57][79][80][81][82]. Several experimental works reported the presence of color centers [53,55], voids [57,80], and oxygen [52,81] in laser-ablated glasses and also self-trapped excitons [71,79], which influence energy transport and lattice defect formation [31,32]. It is also known that oxygen vacancies lead to the narrowing of the material band gap [52,55,83,84].…”
Section: Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of the chemistry in laser-induced structural glass modification was addressed in many studies [52][53][54][55][56][57][79][80][81][82]. Several experimental works reported the presence of color centers [53,55], voids [57,80], and oxygen [52,81] in laser-ablated glasses and also self-trapped excitons [71,79], which influence energy transport and lattice defect formation [31,32]. It is also known that oxygen vacancies lead to the narrowing of the material band gap [52,55,83,84].…”
Section: Numerical Modelmentioning
confidence: 99%
“…In fact, this dependency cannot be explained by corresponding changes of the refractive index [43]. It was also reported that longitudinal periodicity of nanogratings could be explained by interference of short-living exciton polaritons [31,32]. In contrast to plasma wave [1] and nanoplasmonic models [2,4], this approach requires low electron densities, as at higher densities the exciton-polariton interaction is heavily screened by the electron plasma when it begins to efficiently absorb laser energy [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to record and read several layers of information via nanogratings was demonstrated by Shimotsuma et al [8]. Later it was demonstrated that digital information can be independently recorded simultaneously in retardance and slow axis orientation [9]. The retardance can be controlled with a precision of about 10 nm, while slow axis angle can be defined with a few degree precision.…”
mentioning
confidence: 99%
“…21,22 Despite many hypotheses to explain the mechanism of the peculiar self-organization, the formation of the periodic nanostructures remains under debate giving the ideas of seeding processes governed by the randomly distributed inhomogeneity. 21,[23][24][25][26][27][28][29] Recently it was demonstrated that these nanostructures are nanoporous planes filled with decomposed SiO 2 and oxygen. 30,31 Such a periodic assembly behaves as a uniaxial birefringent material with the optical axis oriented parallel to the polarization of incident laser beam.…”
Section: Introductionmentioning
confidence: 99%